Representations of Banach algebras as algebras of completely bounded maps - Oikhberg, Timur (MATHEMATICA SCANDINAVICA, 2009)
We use the notion of Π_2-hyperreflexivity to construct, for a wide variety of Banach algebras A, an operator space X and a representation π : A → CB(X), such that CB(X) consists of 2-summing perturbations of π(A). This gives rise to some examples of operator spaces with interesting properties.